A Thematic Review on Blockchain Suitability in Inter-Organisational Collaboration Workflow In E-Payment Process in the Malaysian Public Sector - Naharudin Saadan; Khairil Faizal Khairi; Azuan Ahmad; Agoos Munalis Tahir (www.amertainstitute.com, 2024)
Blockchain Technology (BCT) has emerged as a transformative tool for enhancing inter-organisational collaboration (IOC) workflows, particularly in complex, multi-stakeholder environments such as the public sector’s electronic payment (e-payment) systems. In Malaysia, e-payment processes are a critical component of the government’s digital transformation agenda, as outlined in the MYDigital blueprint. However, significant challenges persist in managing IOC workflows, with fragmented operational systems and reliance on manual processes undermining the efficiency and reliability of transactions among government agencies, acquiring banks, and the accounting office. The 2022 Auditor General’s Report highlighted systemic inefficiencies, revealing that acquiring banks and collection agents frequently failed to meet service provision timelines, leading to delays in transferring over RM6.0 billion in government-collected funds between 2015 and 2020. These delays underscore the limitations of the current system, including service discrepancies, operational complexity, and inadequate communication. Given BCT’s inherent features—transparency, decentralisation, immutability, and automation—it offers a promising solution to these persistent issues. This study aims to (i) identify trends and statistics in BCT-related research within the construction industry from 2017 to 2024 and (ii) evaluate key topics within BCT literature relevant to IOC workflows. Using a systematic search and screening process across major databases (Scopus and Mendeley), 35 eligible articles were selected for analysis. A thematic analysis, conducted with ATLAS.ti 24, identified seven critical themes: autonomous penalties enforcement, middleware for fragmented systems, automation of manual processes, SLA monitoring platforms, legality of smart contracts, reduction of operational complexity, and improvement of IOC workflow communication. The findings offer valuable insights into BCT’s suitability for addressing IOC workflow challenges and highlight potential avenues for future research. These insights are expected to guide public sector organisations in accelerating the adoption of BCT as a solution for improving e-payment processes and enhancing overall operational efficiency.